Historical archaeology of early modern colonialism in Asia-Pacific. - Cruz Berrocal, María; Zang, Zhenhua (University Press of Florida, 2017)
This book puts together archaeological and historical visions from scholars from Europe, Asia and America, to contribute new data and perspectives to the fairly little known topic of the early colonial endeavors in Asia-Pacific and the Pacific.